Placental transfer of total IgG and IgG subclasses in a Turkish population living in eastern Anatolia - Akbulut, Handan; Çelik, Ilhami; Çelik, Aygen; Akbulut, Ayhan; Ayar, Ahmet (My University, 2012)
Objective: The aim of this comparative clinical study was to investigate the mother-to-baby transfer of immunoglobulin (Ig) G antibody in a Turkish population living in Eastern Anatolia. Material and Method: One hundred three women, at various gestational ages ranging from 32 to 42 weeks, were enrolled to this mother-baby pair cross-sectional study. Levels of total IgG and the four subclasses of IgG were measured in serum samples taken after delivery by use of method of turbidimetric assay and radial immunodiffusion, respectively. Results: When both term and preterm babies were considered cord serum had significantly higher total IgG and IgG1, while having significantly lower IgG2 and IgG3 levels than in maternal sera. The IgG1 were higher and IgG2 were lower in cord sera than in maternal sera for both full-term (37-42 weeks) and pre-term (32-36 weeks) matched pairs. The mean cord/maternal concentration ratio for IgG subclasses were decreased in the order of IgG1>IgG4>IgG3>IgG2 and IgG4>IgG1>IgG3>IgG2 for the full-term and pre-term matched pairs, respectively. No significant correlation was detected between total or subclasses IgG concentrations and gestational age. Conclusion: In this studied Turkish population all four maternal IgG subclasses, IgG1 and IgG4 being more were transported across the placenta from mother to her fetus. The results are relevant to both vaccination and disease surveillance in early infancy.
Do?u anadolu'da yaşayan bir Türk popülasyonu örne?inde total igG ve igG alt tiplerinin plasental transferi
Keywords: Fetal blood; Immunity; Immunoglobulin G; Maternally-acquired immunity